Under the storm : a novel - Carlsson, Christoffer, 1986- (Hogarth, 2024)
"On a cold November night in 1994, a farmhouse burns to the ground. Inside, a young woman is found dead--murdered. To the people in the rural community of Marbäck, it becomes a reference point: a before and after. For ten-year-old Isak Nyqvist, the fire sets in motion something he cannot control, as if a stray spark has found its way inside him, igniting his future into an inferno. The police quickly focus their attention on Edvard Christensson, the boyfriend of the murdered woman and Isak's beloved uncle. After a quick investigation where the evidence speaks for itself, Edvard is sentenced to life in prison and Marbäck believes it can return to its innocence. Vidar Jörgensson, the rookie police officer who was one of the first responders to the fire, prides himself on having contributed to solving the murder. Little does he know this will become the defining case of his career, or that it will drive him to the brink of professional and personal disaster--and link his fate to Isak's"--